1998
DOI: 10.1016/s0304-3959(98)00041-4
|View full text |Cite
|
Sign up to set email alerts
|

The anti-hyperalgesic actions of the cannabinoid anandamide and the putative CB2 receptor agonist palmitoylethanolamide in visceral and somatic inflammatory pain

Abstract: This study assessed the effects of two N-acylethanolamides in established rat models of visceral and somatic inflammatory pain. (1) The therapeutic effects of the cannabinoid anandamide and the putative CB2 agonist palmitoylethanolamide were tested in a model of persistent visceral pain (turpentine inflammation of the urinary bladder). Both anandamide (at a dose of 25 mg/kg) and palmitoylethanolamide (at doses of 10-30 mg/kg) were able to attenuate the viscero-visceral hyper-reflexia (VVH) induced by inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
221
0
10

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(239 citation statements)
references
References 30 publications
6
221
0
10
Order By: Relevance
“…Further support to this proposal comes from the fact that palmitylethanolamide may exert both analgesic Ž . Calignano et al, 1998;Jaggar et al, 1998; present study Ž and anti-inflammatory effects Benvenuti et al, 1968;Facci . et al, 1995;Mazzari et al, 1996 .…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Further support to this proposal comes from the fact that palmitylethanolamide may exert both analgesic Ž . Calignano et al, 1998;Jaggar et al, 1998; present study Ž and anti-inflammatory effects Benvenuti et al, 1968;Facci . et al, 1995;Mazzari et al, 1996 .…”
Section: Discussionmentioning
confidence: 49%
“…rodents Calignano et al, 1998;Jaggar et al, 1998 . In the present study, we have further characterized the antinociceptive activity of this endogenous lipid molecule in several models of phasic and tonic pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, more recent data have indicated that PEA does not bind with high a nity to either of the two cannabinoid receptor subtypes (Showalter et al, 1996;antagonizing in¯ammatory processes (Facci et al, 1995;Mazzari et al, 1996). Furthermore, peripheral administration of PEA produces an analgesic e ect in formalin-induced in¯ammatory pain (Jaggar et al, 1998;Calignano et al, 1998), and the PEA-induced anti-nociceptive e ects are believed to be mediated by a peripheral CB 2 -like receptor. This is of particular pharmacological interest since PEA, in contrast to AEA, has no action on central CB 1 receptors, and so is unlikely to produce unwanted psychotropic e ects.…”
Section: Introductionmentioning
confidence: 99%